2021
DOI: 10.18844/cjes.v16i6.6542
|View full text |Cite
|
Sign up to set email alerts
|

Language teacher practices predicting students’ reading self-efficacy: Jordanian students’ participation in PISA 2018

Abstract: This study investigated the ability of language teachers’ practices to predict self-efficacy in reading among Jordanian students participating in PISA 2018. The study adopted the secondary analysis method by analyzing the responses of 8,963 15-year-old males and females in 313 schools who participated in PISA 2018. Statistically significant differences in students’ perceptions were found in teacher-directed instruction, teacher support for students, teacher motivating students to engage in reading, and enjoyab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Accordingly, reading motivation is often cited as essential for all learners to become proficient readers [27]. Furthermore, this result is consistent with that of Wiltgen [30], as cited by Alzu'bi et al [31], which indicated that reading efficacy is positively correlated with motivation; highly motivated learners read more, and this positively affects their reading skills and strategies, which, in turn, affects their beliefs about themselves as readers and thus their self-efficacy in reading. This study supports the study of Rodriguez Sua [32], which revealed that using cognitive strategies facilitated comprehension of a text, allowing readers to activate their schemata, understand the main ideas, and understand new vocabulary from reading a passage in short stories.…”
Section: The Level Of Reading Motivation Of the Respondentssupporting
confidence: 85%
“…Accordingly, reading motivation is often cited as essential for all learners to become proficient readers [27]. Furthermore, this result is consistent with that of Wiltgen [30], as cited by Alzu'bi et al [31], which indicated that reading efficacy is positively correlated with motivation; highly motivated learners read more, and this positively affects their reading skills and strategies, which, in turn, affects their beliefs about themselves as readers and thus their self-efficacy in reading. This study supports the study of Rodriguez Sua [32], which revealed that using cognitive strategies facilitated comprehension of a text, allowing readers to activate their schemata, understand the main ideas, and understand new vocabulary from reading a passage in short stories.…”
Section: The Level Of Reading Motivation Of the Respondentssupporting
confidence: 85%
“…This finding is in line with the statement of Hidayati, Inderawati, and Loeneto (2020). Critical reading skill is strongly correlated with critical thinking (Alzubi and Attiat 2021;Fikriyatii, Agustini, & Sutoyo, 2022). A critical thinking skill demonstrated through the expertise in reading HOTS questions becomes a very important skill in education in the 21st century (Changwong, Sukkamart, & Sisan, 2018;Ulger 2018 ;Ridho, Wardani, & Saptono, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The MCA reading literacy questions measure the students' skills at a high level of thinking, namely being able to process information, evaluate, and make noise (Alzubi & Attiat, 2021;Ningsyih et al, 2022;Rufaidah & Junaidi, 2021;Setyowati, Kristiani, & Murwaningsih, 2022;Zahrudin, Ismail, & Zakiah, 2021). Therefore, the proportion of each level of thinking ability in each question item must be considered.…”
Section: Introductionmentioning
confidence: 99%